Mekanisme Pengimpunan dan Pendistribusian Zakat Fitrah di Masjid AL-Ikhlas Pawosoi Kec. Wotu Kab. Luwu Timur - Suardi, Aqilla Nur Fadia Ardi; Yusuf, Hardianti (Institut Agama Islam Negeri Parepare, 2022)
The aim of this study was to ascertain the mechanism for collecting and distributing zakat fitrah at Masjid al-Ikhlas Pawosoi, located in Kec. Wotu, Kab. East Luwu. The research employed a field research approach utilizing qualitative descriptive methods. The methodology encompassed qualitative data analysis through interviews and documentation. The findings revealed the following: 1) The management of zakat fitrah at Masjid al-Ikhlas Pawosoi, Kec. Wotu, Kab. East Luwu, can be classified as moderate and standard, as it has fulfilled the aspects of collection and distribution. Nevertheless, concerning distribution, optimization is yet to be achieved due to the absence of definitive criteria for zakat recipients. Mustahik are solely chosen and recorded in accordance with observations made by the Mosque's Imam as the Amil Zakat. Moreover, both the Amil Zakat and the Zakat Committee consist of capable and experienced individuals. 2) The collection process has been executed effectively, with each Muzakki fulfilling their zakat fitrah obligation based on their understanding of its mandatory nature. Challenges such as Muzakki paying zakat outside the mosque have been addressed by proactively visiting the Muzakki's residence and directly confirming whether zakat has been paid. 3) The distribution of Zakat, or the dispensation of zakat, occurs around Masjid al-Ikhlas, Kec. Wotu, Kab. East Luwu, preferably before the Eid prayers but generally during the takbiran period. 4) The empowerment of zakat has yet to be realized, as the distribution of zakat is still primarily intended for consumptive purposes.